1977
DOI: 10.7326/0003-4819-86-3-301
|View full text |Cite
|
Sign up to set email alerts
|

Acute Intravascular Hemolysis and Acute Liver Failure Associated as a First Manifestation of Wilson's Disease

Abstract: In three patients, the first manifestation of Wilson's disease was a syndrome in which acute intravascular hemolysis and acute liver failure were associated. This syndrome developed in three periods; the first, lasting 3 to 14 days, was characterized by fatigue, fever, and jaundice; the second, lasting 1 or 2 days, by severe intravascular hemolysis; and the third, lasting 2 to 6 days, by hepatic encephalopathy. All of the patients died from liver failure 7 to 21 days after the onset of the syndrome. The associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(46 citation statements)
references
References 15 publications
4
42
0
Order By: Relevance
“…Nonimmune hemolysis is well Liver Transplantation for Wilson' s Disease described in patients with fulminant Wilson' s disease. 28,33,34 Seventy percent of our patients with FHF or SHF presented with hemolysis. This complication was not present in the patients with CHF.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Nonimmune hemolysis is well Liver Transplantation for Wilson' s Disease described in patients with fulminant Wilson' s disease. 28,33,34 Seventy percent of our patients with FHF or SHF presented with hemolysis. This complication was not present in the patients with CHF.…”
Section: Discussionmentioning
confidence: 92%
“…12 FHF can occur as the initial presentation of the disease in otherwise asymptomatic patients. [26][27][28] Under these circumstances, liver transplantation appears to be the treatment of choice, with correction of the complications of liver failure and acceptable longterm outcomes. Since the first successful liver transplantation for Wilson' s disease in 1969, 29 a number of reports have been accumulated in the literature, addressing the role of transplantation in survival and reversibility of biochemical, 10,19,30 radiological, [20][21][22][23][24][25][26][27][28][29][30][31] and neurological 14,19,32 manifestations of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with WD, liver dysfunction after hemolytic anemia was sometimes observed as an initial clinical manifestation similar to LEC rats (20,21). As to the cause of hemolysis in WD patients, it was suggested that increased circulation of inorganic copper ions damaged erythrocyte membranes (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…This copper is taken up by red cells which then become much more prone to lysis, possibly because the amount of reduced glutathione is decreased, and consequently, the cell is vulnerable to oxidative damage. 7,10,13,15,16 Ozsoylu 21 noted a marked deficiency of vitamin E in one patient with Wilson's disease and hemolytic anemia, and suggested that this may also be a factor leading to oxidative damage. 21 The serum copper level in Patient 1 was only slightly below the lower limit of the reference interval, and higher than levels usually associated with Wilson's disease (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Patient 1 showed the typical dramatic fulminant course that has been reported by others. 7,[9][10][11][12][13][14][15][16][17] This differs, of course, from the usual mode of presentation in childhood chronic liver disease. 3,4,18,19 Diagnosis of Wilson's disease in this patient was based on the presence of Kayser-Fleischer rings, a low serum ceruloplas-min level, and elevated urinary copper excretion.…”
Section: Discussionmentioning
confidence: 99%